Dark triad personality traits are associated with decreased grey matter volumes in ‘social brain’ structures - Myznikov, Artem; Korotkov, Alexander; Zheltyakova, Maya; Kiselev, Vladimir; Masharipov, Ruslan; Bursov, Kirill; Yagmurov, Orazmurad; Votinov, Mikhail; Cherednichenko, Denis; Didur, Michael; Kireev, Maxim (Frontiers in Psychology, 2024)
Introduction Personality traits and the degree of their prominence determine various aspects of social interactions. Some of the most socially relevant traits constitute the Dark Triad – narcissism, psychopathy, and Machiavellianism – associated with antisocial behaviour, disregard for moral norms, and a tendency to manipulation. Sufficient data point at the existence of Dark Triad ‘profiles’ distinguished by trait prominence. Currently, neuroimaging studies have mainly concentrated on the neuroanatomy of individual dark traits, while the Dark Triad profile structure has been mostly overlooked. Methods We performed a clustering analysis of the Dirty Dozen Dark Triad questionnaire scores of 129 healthy subjects using the k-means method. The variance ratio criterion (VRC) was used to determine the optimal number of clusters for the current data. The two-sample t-test within the framework of voxel-based morphometry (VBM) was performed to test the hypothesised differences in grey matter volume (GMV) for the obtained groups. Results Clustering analysis revealed 2 groups of subjects, both with low-to-mid and mid-to-high levels of Dark Triad traits prominence. A further VBM analysis of these groups showed that a higher level of Dark Triad traits may manifest itself in decreased grey matter volumes in the areas related to emotional regulation (the dorsolateral prefrontal cortex, the cingulate cortex), as well as those included in the reward system (the ventral striatum, the orbitofrontal cortex). Discussion The obtained results shed light on the neurobiological basis underlying social interactions associated with the Dark Triad and its profiles.